Pemberdayaan Masyarakat Berbasis Kelompok Melalui Pelatihan Pertanian Berkelanjutan dan Pengembangan Usaha Mikro untuk Mewujudkan Ketahanan Pangan di Desa Lumban Gurning - Monalisa Br Samosir; Herryanto Sinaga; Elman Vian Zaluhku; Stefan Boby Sigalingging; Yosafat Sihombing; Eben Oktavinus Zai (Lembaga Pengembangan Kinerja Dosen, 2025)
Community empowerment based on groups is an effective strategy to achieve food security in Lumban Gurning Village. This study aims to identify the potential and challenges in increasing food availability. With a participatory approach, community groups were formed to manage local resources sustainably. Data were collected through in-depth interviews, focus group discussions, field observations, and surveys. The analysis was conducted using the SWOT method and descriptive analysis. The results showed that empowerment groups were able to increase food production, diversify crops, and reduce dependence on external food. This initiative also raised awareness of the importance of a healthy diet and balanced nutrition, and facilitated the use of information technology for marketing local products. However, challenges such as access to capital, unmet weather, and infrastructure still need to be overcome. Collaboration between the government, non-governmental organizations, and the private sector is needed to support the absence of this program. By strengthening the capacity of community groups, it is hoped that Lumban Gurning Village can achieve better food security and encourage sustainable development.